2014
DOI: 10.1186/1758-5996-6-113
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate improves insulin resistance evaluated using the glucose clamp technique in patients with type 2 diabetes mellitus: a small-scale clinical study

Abstract: BackgroundBezafibrate is mainly used to treat hypertriglyceridemia. Studies have reported that bezafibrate also improves type 2 diabetes mellitus, but the mechanism has not been fully elucidated. We performed euglycemic hyperinsulinemic clamps (glucose clamp) and meal tolerance tests (MTT) to examine the effects of bezafibrate on insulin resistance in patients with type 2 diabetes mellitus.MethodsTwelve Japanese patients with type 2 diabetes mellitus and dyslipidemia (mean age: 59.5 years; fasting plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Conclusive evidence regarding the effects of PPARα agonists on insulin sensitivity was not established. Bezafibrate decreased the HOMA‐IR and increased the PGU in patients with type 2 diabetes. This finding might be attributed to the low PPARα selectivity and partial PPARγ agonistic activity, albeit weak, of bezafibrate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conclusive evidence regarding the effects of PPARα agonists on insulin sensitivity was not established. Bezafibrate decreased the HOMA‐IR and increased the PGU in patients with type 2 diabetes. This finding might be attributed to the low PPARα selectivity and partial PPARγ agonistic activity, albeit weak, of bezafibrate.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, PPARα agonists, also known as fibrates, stimulate FA oxidation, suppress FA and TG synthesis, and reduce plasma TG or TG‐rich lipoprotein levels. However, previous studies showed inconsistent results regarding the effects of PPARα agonists on glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of glycemic parameters, the post hoc repeated-measures ANCOVA showed that pemafibrate decreased the fasting glucose, insulin, and HOMA-IR levels, although the prespecified analyses did not show a clear trend. The results of previous studies on the effects of PPARa agonists other than pemafibrate on IR were inconsistent (31)(32)(33)(34)(35). Pemafibrate has been suggested to improve IR in the hyperinsulinemic-euglycemic-clamp study (36) and pooled analyses of previous studies (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that bezafibrate, another drug of fibrates, also displayed some beneficial effects on insulin resistance and glucose metabolism in patients with type 2 diabetes [ 35 ]. Different from fenofibrate, bezafibrate is a pan PPAR agonist and activates three PPAR subtypes including PPAR α , PPAR δ , and PPAR γ [ 36 ].…”
Section: Discussionmentioning
confidence: 99%